The Trillion Dollar War The U.S. Effort to Rebuild Afghanistan, 1999-2021 - Amiri, Abid (Marine Corps University Press (MCUP), 2021)
What if the U.S. war on terror in Afghanistan was fought not by the military but by educating the Afghan youth, and what if the trillion dollars had been spent instead on economic development in Afghanistan rather than on bombs and fighter jets? The Trillion Dollar War helps explain the United States' efforts to rebuild Afghanistan during the last 20 years. The book outlines the successes and failures of both Afghans and Americans in this endeavor. In addition, it provides an in-depth analysis of the cost of America's longest war, and it asks whether spending more on education and infrastructure than on weapons of war would have resulted in a different outcome.